Do Corrupt Local Governments Inhibit Entrepreneurship? A Contextual Analysis of Start-Ups in Swedish Municipalities - Emanuel Wittberg; Gissur Ó. Erlingsson (Research Institute of Industrial Economics (IFN), 2020)
Does corruption affect the incentives for potential entrepreneurs to start businesses? The traditional view holds that entrepreneurship is inhibited. However, a few recent studies indicate the contrary, supporting a "grease the wheels" perspective. In a novel approach to this question, we combine a local government corruption index and individual-level register data on start-ups in a low-corruption setting: Sweden. We disaggregate the analysis to individual entrepreneurs, focus on corruption in local institutions and hypothesize that local corruption deters potential entrepreneurs. Our findings are twofold. First, rejecting the "grease the wheels" hypothesis, local corruption has a strong local deterring effect on potential entrepreneurs. Second, a minority of entrepreneurs relocate their start-ups from home municipalities to elsewhere. However, contrary to expectations, relocaters could embody "non-productive" or "destructive" entrepreneurship: they migrate from relatively low-corrupt to relatively high-corrupt municipalities. While migrating is uncommon, and the effect is weak, it nonetheless indicates that relocaters are attracted to conditions where rent-seeking opportunities are present.
Keywords: D73; L26; 330; Entrepreneurship; Start-ups; Corruption; Local government; Destructive entrepreneurship